Effects of gadolinium‐based MRI contrast agents on liver tissue. Issue 5 (1st April 2018) - Mercantepe, Tolga; Tümkaya, Levent; Çeliker, Fatma Beyazal; Topal Suzan, Zehra; Çinar, Seda; Akyildiz, Kerimali; Mercantepe, Filiz; Yilmaz, Adnan
Abstract : Background: MRI with contrast is often used clinically. However, recent studies have reported a high accumulation of gadolinium‐based contrast agents (GBCAs) in kidney, liver, and spleen tissues in several mouse models. Purpose: To compare the effects on liver tissue of gadolinium‐based MRI contrast agents in the light of biochemical and histopathological evaluation. Study Type: Institutional Review Board (IRB)‐approved controlled longitudinal study. Animal Model: In all, 32 male Sprague–Dawley rats were divided into a healthy control group subjected to no procedure (Group 1), a sham group (Group 2), a gadodiamide group (Group 3), and a gadoteric acid group (Group 4). Field Strength/Sequence: Not applicable. Assessment: Liver tissues removed at the end of the fifth week and evaluated pathologically (scored Knodell's histological activity index [HAI] method by two histopathologists) immunohistochemical (caspase‐3 and biochemical tests (AST, ALT, TAS, TOS, and OSI method by Erel et al) were obtained. Statistical Tests: Differences between groups were analyzed using the nonparametric Kruskal–Wallis test followed by the Tamhane test, and one‐way analysis of variance (ANOVA) followed by Turkey's HSD test. Results: An increase was observed in histological activity scores in sections from rats administered gadodiamide and gadoteric acid, and in caspase‐3, AST and ALT values ( P  < 0.05). In contrast, we determined no change in TOS ( P  = 0.568 and P  = 0.094, respectively), TAS ( P  = 0.151 and P  = 0.055, respectively), or OSI ( P  = 0.949 and P  = 0.494, respectively) values. Data Conclusion: These data suggest that gadodiamide and gadoteric acid trigger hepatocellular necrosis and apoptosis by causing damage in hepatocytes, although no change occurs in total antioxidant and antioxidant capacity. Level of Evidence: 1 Technical Efficacy: Stage 4 J. Magn. Reson. Imaging 2018;47:1367–1374.